Trade liberalisation and the Jamaican economy : implications of tariff adjustments - Hudson, Suzette (Caribbean Centre for Monetary Studies [St. Augustine]TT, 2003)
Reviews the trends in international negotiations with a view to identifying the time frame within which tariffs are likely to be adjusted. Traces the evolution and extent of trade liberalisation in Jamaica and assesses the prospects for further liberalisation in the near to medium term.